A randomized, open-label, single-dose, two-cycle crossover study to evaluate the bioequivalence and safety of lenvatinib and Lenvima® in Chinese healthy subjects. (3rd July 2022) - Xu, Zhongnan; Wang, Yanli; Liu, Guangwen; Chen, Jiahui; Wang, Wanhua; Cheng, Yang; Ren, Qing; Cui, Yingzi; Yang, Wei; Liu, Zhengzhi; Chen, Xuesong; Xue, Jinling; et al.
ABSTRACT: Background: Lenvatinib is a tyrosine kinase receptor inhibitor that inhibits vascular and endothelial growth factor receptor kinase activity. This study evaluated the bioequivalence and safety of lenvatinib with Lenvima® . Research design and methods: The fasting and postprandial groups were two independent trials. Subjects were randomly divided into two sequences at a ratio of 1:1 for two-cycle crossover administration. Subjects took 10 mg lenvatinib or Lenvima® once per cycle. The wash-out period was 14 days. Detected the plasma drug concentrations and assessed the bioequivalence of two drugs. Besides, we evaluated the safety of the drugs throughout the trial. Results: In the fasting state, the GMRs of Cmax, AUC0-t, and AUC0-∞ were 99.89%, 102.98% and 103.19%, respectively. The 90% CIs were all within 80%-125%. In the postprandial state, the GMRs of Cmax, AUC0-t, and AUC0-∞ were 98.96%, 94.25% and 95.27%, respectively. The 90% CIs were all within 80%-125%. All results met the bioequivalence criteria. Both drugs had good safety and tolerance in this trial. Conclusion: This study showed that lenvatinib and Lenvima® had similar bioequivalence and safety in healthy Chinese subjects under fasting and postprandial conditions. Clinical trial registration: This trial is registered at the Chinese Clinical Trial website (http://www.chinadrugtrials.org.cn/index.html # CTR20191172)